Security in Computer and Information Sciences: Second International Symposium, EuroCybersec 2021, Nice, France, October 25–26, 2021, Revised Selected Papers - Gelenbe, Erol; Jankovic, Marija; Kehagias, Dionysios; Marton, Anna; Vilmos, Andras (Communications in Computer and Information Science, 2022)
This open access book constitutes the thoroughly refereed proceedings of the Second International Symposium on Computer and Information Sciences, EuroCybersec 2021, held in Nice, France, in October 2021. The 9 papers presented together with 1 invited paper were carefully reviewed and selected from 21 submissions. The papers focus on topics of security of distributed interconnected systems, software systems, Internet of Things, health informatics systems, energy systems, digital cities, digital economy, mobile networks, and the underlying physical and network infrastructures. This is an open access book.